Outcome-based education identifying determining factors in improving students learning achievement in higher education systems - Muhammad Syafri Syamsudin; Indra Maulana (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Education opens up numerous opportunities to record economic expansion worldwide, with specific reference to developing countries. Progress in educational indicators has been inadequate over the past few decades. Outcome-Based Education (OBE) has recently garnered significant attention in Indonesia. OBE is employed in education because it clearly focuses and organizes everything in the education system around what all students need to be able to do by the end of their learning journey. OBE proposes influential and engaging choices to transform and organize medical education. Therefore, the fundamental objective of this review is to highlight the higher education system and the need to transition from a teacher-centered system to an outcome-based education system. This review also discusses the key factors that influence student learning outcomes. The search strategies were designed by combining Boolean operators and key terms relevant to the review objectives. Five studies were included in the paper regarding the effectiveness of Outcome-Based Education in various educational disciplines. The findings suggest five important factors from the literature that influence student learning outcomes, including assessment strategies, learning objectives based on complexity levels, preferred learning styles of students, English language proficiency, and industry requirements.